Teoria dos números aplicada a resolução de problemas em uma sala de 6º ano da Escola Professora Oneide Alves Pinheiro de Nova Timboteua, Pará - FONSECA, Raquel Nery (2022)
The present study focuses on Number Theory applied to problem solving to 6th graders of Elementary School at Oneide Alves Pinheiro School in Nova Timboteua-Pa. The main objective is to investigate how number theory can contribute to the resolution of problem situations and consequently to the learning of students in elementary school. In order to achieve this objective, this study is part of the bibliographic and quantitative research. As for its structure the study is divided into four chapters. The first deals with an initial analysis of Number Theory. The second deals with the insertion of this theory in elementary school. The third presents the research methodology and the fourth to the data analysis. The results revealed that in the researched class students have difficulties in solving problems, their acquisition on the other hand would allow students to develop autonomy and critical sense in them. The research also revealed that number theory should be worked out more contextually in the educational environment as a way to enable students to use their knowledge to solve problems. Thus, it is noticeable that the theory of numbers is more valued in the learning process of students, especially in situations involving the correlation between theory and practice.